Development of the modified zeolite -A catalyst for the direct conversion of methane too liquid hydrocarbons - Mohammad Afifi Faiz, Azha @ Azahar (2008)
The characteristic of ZeoliteA loaded with iron and zinc on the direct conversion of methane to liquid hydrocarbons is investigated. ZeoliteA is loaded with different mass ratio of zinc and iron. Thermo Gravimetric Analysis (TGA), XRay Diffraction (XRD), and Fourier transform spectroscopy (FTIR) are used to analyze the physicochemical properties of the modified zeolite such as functional group, surface area and average diameter of unit cell. The absence of the iron content in the catalyst does not affect the framework and the crystalline of the catalyst but only affect the size of the unit cell and the surface area of the catalyst. As compare to zinc, it has modified the crystalline and framework of the catalyst. The result indicated that ZeoliteA with 8% of zinc and 2% of iron of metal doped is the most suitable catalyst for the methane conversion to liquid hydrocarbons. The catalyst has high thermal stability, high surface area, and high average diameter of unit cell and has low weight loss.